Production and modification of nanofibrillated cellulose using various mechanical processes: a review - Abdul Khalil, H. P. S.; Davoudpour, Yalda; Islam, Md. Nazrul; Mustapha, Asniza; Sudesh, Kumar; Dungania, Rudi; Jawaid, Mohammad (Elsevier, 2014)
Nanofibrillated cellulose from biomass has recently gained attention owing to their biodegradable nature, low density, high mechanical properties, economic value and renewability. Although they still suffer from two major drawbacks. The first challenge is the exploration of raw materials and its application in nanocomposites production. Second one is high energy consumption regarding the mechanical fibrillation. However, pretreatments before mechanical isolation can overcome this problem. Hydrophilic nature of nano-size cellulose fibers restricts good dispersion of these materials in hydrophobic polymers and therefore, leads to lower mechanical properties. Surface modification before or after mechanical defibrillation could be a solution for this problem. Additionally, drying affects the size of nanofibers and its properties which needs to study further. This review focuses on recent developments in pretreatments, nanofibrillated cellulose production and its application in nanopaper applications, coating additives, security papers, food packaging, and surface modifications and also for first time its drying.